Evaluation of leaf surface structure and control of Conyza spp. by herbicides applied in soybean pre-plant burndown - Silva, P V da; Medeiros, E S de; Schedenffeldt, B F [UNESP]; Salmazo, P A V; Borges, R P N; Munaro, F C; Mauad, M; Khan, S; Silva, G P; Monquero, P A; Dias, R D C (FapUNIFESP (SciELO), 2025)
The pre-plant burndown of Conyza spp. is a fundamental practice to mitigate weed competition with soybean. However, in light of reports of biotypes resistant to 2,4-D, the search for new options of post-emergent herbicides becomes essential. The objective of the present study was to evaluate the effect of post-emergent herbicides on the leaf structure and chemical control of Conyza spp. with heights greater than 10 cm in soybean pre-plant desiccation. A field experiment was conducted following a randomized block design, with seven treatments and four replicates. For the control data, only mesotrione + atrazine and chlorimuron resulted in control percentages lower than 80%. Regarding scanning electron microscopy (SEM), trichomes were denser on the adaxial leaf surface, while stomata predominated on the abaxial side, though both were present on both surfaces. Their distribution showed tendencies of clustering and randomness, with no consistent pattern linked to the treatments. Slight, non-significant variations in trichome density occurred, especially with halauxifen + diclosulam. The control and halauxifen + diclosulam treatments exhibited higher trichome intensity and less structural damage, whereas fluroxypyr + clethodim, dicamba, and triclopyr resulted in lower intensity and trichome disruption. Consequently, fluroxypyr + clethodim, triclopyr, dicamba, and halauxifen + diclosulam were effective in desiccating Conyza spp., with the first two causing trichome damage via plasmolysis.